Efficacy of Varied Doses of Papaya (Carica papaya) Leaf Extract in Controlling Argulus Infestation in Comet Fish (Carassius auratus) - Oktaviona, Maulidya; Desrina, Desrina; Haditomo, Alfabetian Harjuno Condro (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2025)
This study used papaya leaf extract as an environment-friendly treatment for parasitic infections. This investment method is simple, rapid, and affordable. Papaya leaf extract of 100 ppt was produced by boiling for 15 min at 90°C. This study aimed to determine the effectiveness and optimal concentration of papaya leaf extract (C. papaya) as a control against Argulus infestation in the comet fish (C. auratus). The study was conducted over 30 days. The research method used a completely randomized design with four treatments and three replications, consisting of papaya leaf extract dosage (ml extract/water) in treatments A (0 ml/l), B (7 ml/l), C (14 ml/l), and D (21 ml/l). A per aquarium was introduced with 10 Argulus for 4 days to induce infection in fish. The treatment was applied by soaking for 60 min and observing for 7 days. The parameters observed were clinical symptoms, absolute weight, absolute length, survival rate, Argulus behavior, Argulus detachment, and water quality. Clinical symptoms in fish include excess mucus and lesions in certain parts of the body. Absolute length was 4.83±0.20 cm and absolute weight were 1.30±0.12 g. Argulus behavior with time of attachment was 2.55-9.35 minutes. The survival rate of comet fish in treatment A was 86.67%, whereas that of treatments B, C, and D was 100%. Argulus detachment rates were significantly different (P<0.05) among treatments A (0%), B (16.67%), C (33.33%), and D (70%). The results showed that the immersion of papaya leaf extract effectively released Argulus from comet fish, with the highest Argulus release obtained in treatment D (21 ml/l).